Enhancement of the Qos in an Ofdma/Vlc System - Soto-Gomez, J; Adasme-Soto, P; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2016)
A resource allocation optimization for indoor Optical Wireless Communications is proposed. A smart coordinator tries to maximize the channel capacity by enabling or disabling the communication of the devices subject to system constraints. Binary Cuckoo Search and Genetic Algorithms were used in order to solve the binary NP-HARD optimization problem. The results show that the total channel capacity slowly decrease while the number of users increase. On the other hand, per-user capacity decrease faster than the total capacity. The minimum QoS of the system is achieved. Binary Cuckoo Search overcomes Genetic Algorithms when dealing with the proposed optimization problem. © 2016 IEEE.